Evaluation of near-infrared spectroscopy, transcranial Doppler, and ophthalmic ultrasound measurements in critically Ill pediatric patients with increased intracranial pressure - Yavas, Damla Pinar; Yildizdas, Dincer; Misirlioglu, Merve; Ekinci, Faruk; Incecik, Faruk; Ozgur Horoz, Ozden (Frontiers in Pediatrics, 2026)
ObjectivesNon-invasive methods are needed to rapidly assess increased ICP, especially for managing patients when invasive devices are unavailable or contraindicated. This study aims to examine the diagnostic value of transcranial Doppler (TCD), ophthalmic ultrasound measurements, and near-infrared spectroscopy (NIRS) to define non-invasive ICP (nICP) in the evaluation of pediatric intensive care unit (PICU) patients with increased ICP.MethodsThis is a Single center prospective case-control study. The study group comprised 32 pediatric patients with increased ICP, while the control group comprised 64 healthy children. The following non-invasive methods were measured prospectively: optic nerve sheath diameter (ONSD)-derived nICP (nICPONSD), central retinal artery Doppler indices, arterial TCD blood velocities, pulsatility index (PI)-derived nICP (nICPPI), Lindegaard ratio (L/R), and NIRS values.ResultsMean ONSD, retinal artery resistive index (RI), middle cerebral artery (MCA) RI, nICPONSD, and L/R were significantly greater in the study group than the control group (p < 0.000, p < 0.000, p < 0.011, p < 0.000, p < 0.000, respectively). There was no significant correlation between ONSD and NIRS values or between MCA PI and NIRS values. The ONSD measurement was the strongest parameter, with an area under the curve (AUC) of 0.92 (95% CI = 0.884–0.986) and the best cut-off value being 5.27 mm (sensitivity = 76.56%; specificity = 96.87%) for detecting increased ICP.ConclusionThe availability and utilization of both TCD and ophthalmic ultrasound methods have recently increased. This is the first pediatric report that focuses on comparing ONSD, TCD, and NIRS and evaluates the Doppler indices in patients with increased ICP.